2002
DOI: 10.1006/viro.2002.1509
|View full text |Cite
|
Sign up to set email alerts
|

The Carboxyl Segment of the Mumps Virus V Protein Associates with Stat Proteins in Vitro Via a Tryptophan-Rich Motif

Abstract: Viruses of the Paramyxovirinae, similar to other viruses, have evolved specific proteins that interdict IFN action as part of a general strategy to counteract host innate immunity. In many (but not all) cases, this interdiction is accompanied by a lowering of the intracellular levels of the STAT proteins. Among rubulaviruses, there is a notable variation in how they interfere with IFN action. Whereas SV41, SV5, and MuV all act by lowering Stat1, hPIV2 acts by lowering Stat2. Here, we show that the mumps and hP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 44 publications
2
54
0
Order By: Relevance
“…It is possible that these factors might have led to the discrepancy (16,17). In contrast to the STAT degradationindependent mechanism presented here, Garcin et al emphasized the degradation of STAT1 in SeV-infected MEF cells as an SeV blocking mechanism for IFN signaling and attempted to find the common denominator between functions of SeV C protein and rubulavirus V proteins (10,11,13,30). Longer C protein-specific degradation of STAT1 in NIH 3T3 mouse MEF cells, however, appears to be a special case.…”
Section: Fig 8 Stat1mentioning
confidence: 67%
See 1 more Smart Citation
“…It is possible that these factors might have led to the discrepancy (16,17). In contrast to the STAT degradationindependent mechanism presented here, Garcin et al emphasized the degradation of STAT1 in SeV-infected MEF cells as an SeV blocking mechanism for IFN signaling and attempted to find the common denominator between functions of SeV C protein and rubulavirus V proteins (10,11,13,30). Longer C protein-specific degradation of STAT1 in NIH 3T3 mouse MEF cells, however, appears to be a special case.…”
Section: Fig 8 Stat1mentioning
confidence: 67%
“…The V protein of rubulavirus simian virus 5 targets a key factor, signal transducer and activator of transcription 1 (STAT1), on interferon (IFN) signaling for proteasome-mediated degradation, thereby inhibiting IFN signal transduction (1,3,6,7,33,35,48,49). The V proteins of other rubulaviruses, including human parainfluenza virus type 2, mumps virus, and simian virus 41 inhibit IFN signaling likewise by inducing a decrease in the STAT1 or STAT2 level (8,25,30,31,34,35,47,49). In contrast, the respirovirus Sendai virus (SeV), which possesses both V and C ORFs, has evolved functions of the C protein instead of the V protein so as to block IFN signaling (12,18).…”
mentioning
confidence: 99%
“…However, the interaction between IKKe and V reported here is not mediated by STAT1 because V M could block TLR3 signaling in U3B cells (42), which lack functional STAT1 (data not shown). The tryptophan residues of V that were required for IKKe binding are located in the C-terminal region of the protein (43). Because this region is not shared between viral V and P proteins, whose mRNAs are produced by alternative transcription of the same open reading frame, P proteins are not expected to bind to IKKe.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all rubulavirus V proteins target STAT1 or STAT2 for degradation by the host-cell proteosomal pathways [84][85][86][87] through assembly of a V-degradation complex (VDC) containing V protein, STAT1, STAT2, and components of an E3 ubiquitin ligase complex, specifically the UV damage-specific DNA binding protein 1 (DDB1), and Cul4A [88][89][90][91][92] , which likely mediate the STAT1/2 polyubiquitination [93] . In vitro studies/crystallographic analysis of the PIV5 V-DBB1 complex have indicated that both the N-terminal and unique C-terminal regions of PIV5 V are required for VDC assembly and STAT1 degradation [33,88,93,94] .…”
Section: Targeting Of Stats By Rubulaviruses: Degradation and Mis-locmentioning
confidence: 99%